Institutional Provision of the State Regulatory Policy in Ukraine - GLUSHKO, Alina; MARCHYSHYNETS, Olga (Journal of Advanced Research in Law and Economics, 2018)
The article substantiates the necessity of using an institutional approach in the study of the state regulatory policy in the conditions of transformational processes in the national economy. A state regulatory policy is described as a complex multicomponent system. The interrelation of its subjects and objects is determined. The authors define the concept of ‘state regulatory policy’, according to which a state regulatory policy is a normative form of realization of the functions of the subjects of the regulatory processes in the national economy to ensure the socio-economic development of the country and to increase the well-being of its citizens in the conditions of the deepening globalization processes. The authors substantiate the necessity to clarify the conceptual and categorical apparatus during the research of institutional character. The essence of the concepts ‘institute’, ‘institution’ and ‘institutional provision’ is revealed. It is proved that under the institutional provision of the state regulatory policy one should understand the totality of state and non-state institutions that ensure the availability of legal, organizational and economic conditions, which are necessary for the formation and implementation of an effective state regulatory policy. The institutional-legal, institutional-organizational and institutional-personnel provision of the state regulatory policy is characterized. The main existing problematic aspects of institutional provision of the state regulatory policy in Ukraine are outlined and the necessity of an integrated approach to introducing qualitative changes in institutional-legal, institutional-organizational and institutional-personnel provision is substantiated